Flow curvature effects on the parallel velocity shear driven instability: MHD simulations. Issue 7 (3rd August 2019) - Lin, D.; Scales, W.; Sen, S.
ABSTRACT: This paper presents results of magnetohydrodynamic (MHD) simulations of flow curvature effects on the parallel velocity shear (PVS) driven instability in a magnetized plasma. Three flow profiles with identical velocity shear but different velocity curvature: positive curvature, no curvature, and negative curvature, are investigated with an MHD model. The total velocity jump of the positive curvature flow is 29 % higher than the linear flow, and the total velocity jump of the negative curvature flow is 29 % lower than the linear flow. It is found that by the same simulation time, the flow profile with a positive curvature yields more developed plasma density and magnetic field vortices compared with the other two flow profiles with linear and negative curvature flow profiles. The curvature effects are further quantitatively characterized by examining the transverse perturbations. The transverse kinetic energy growth rate of the positive curvature flow is 19 % higher than the linear flow, and 68 % higher than the negative curvature flow. The difference in growth rate appears to be comparable with the difference in the velocity shear frequency and consistent with previous theoretical work.